Impact of the SARS-CoV-2 pandemic on turnover time and revenue in the endoscopy unit: single-center experience* - Abdelhai Abdelqader (Georg Thieme Verlag KG, 2021)
Background and study aims The SARS-CoV-2 pandemic heavily impacted the New York metro area causing most institutions to either reduce case volume or fully close remaining open units incorporated specific guidelines for procedures lockdown potentially leading to a greater turn-over time. We analyzed the quantitative and financial impact of this lost time on our tertiary care center’s endoscopy unit. Patients and methods This single-center, retrospective study included demographics, procedure details and turn-over times (TOT) from all endoscopic procedures between December 1, 2019 to June 30, 2020. Cases were categorized as pre-COVID-19 group from December 1, 2019 to March 15, 2020 and during COVID-19 (lockdown) group from March 16, 2020 to June 30, 2020. The financial impact was assessed using national averages for reimbursement of outpatient endoscopic procedures provided by Center for Medicare and Medicaid Services. Results A total of 3622 procedures were performed during the study period: 2297 in the pre-COVID-19 period, 1325 in the COVID-19 period, representing a 42.32 % decrease. In the COVID-19 lockdown group, there was a significant increase in TOT in both the general endoscopy cases (18.11 minutes, P = 0.000) and advanced endoscopy cases (17.7 minutes, P = 0.000). The 42.3 % decrease in volume equated to at least $1.6 million USD in lost revenue during the lockdown. Conclusions COVID-19 pandemic led to an increase in TOT with overall reduced procedure volume and a negative effect on revenue. Providing continued endoscopic management during a pandemic avoids delays in reopening the endoscopy unit and hampers the post-pandemic surge of delayed cases and its financial impact.